PARADIGMA PENDIDIKAN BERBASIS AKHLAK TASAWUF - Hasibuan, Armyn (AIN Padangsidimpuan, 2014)
AbstractSufism moral-based education paradigm is shaped purely conceptual studies offer ideas who want to build a whole person. Competency-based curriculum and character-based curriculum emphasizes the concept that only a social reality that has its disadvantages. Character of education needs to be a deeper meaning and should be enriched by elements of corresponding to the frame of Islamic education, they are Sufism and morals. As national education, it serves to develop the ability and character development and civilization of dignity in the context of the intellectual life of the nation, it aims to develop the potential learners become religious, healthy, knowledgeable, capable, creative, independent, and become citizens of a democratic and responsible. Sufism morals-based education is offered to orient and focus the moral of Sufism based curriculum, hiring teachers that teacher candidates must pass examinations that support teacher competence, both in the field of social and human decency. Integration and interconnective learning become one of the most important thing because the moral foundation of knowledge of Sufism as an established religion. So privatization law and legality to be one way to realize the goal of national education at the government so that the supremacy of law achieves a healthy life and hereafter.Keyword: Paradigm, Education and Sufism